The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3390/antiox11091838
|View full text |Cite
|
Sign up to set email alerts
|

Eugenol Attenuates Transmissible Gastroenteritis Virus-Induced Oxidative Stress and Apoptosis Via ROS-NRF2-ARE Signaling

Abstract: Transmissible gastroenteritis virus (TGEV), a coronavirus that causes severe diarrhea due to oxidative stress in the piglet intestine, is a major cause of economic loss in the livestock industry. However, limited interventions have been shown to be effective in the treatment of TGEV. Here, we demonstrate the therapeutic activity of eugenol in TGEV-induced intestinal oxidative stress and apoptosis. Our data show that eugenol supplementation protects intestine and IPEC-J2 cells from TGEV-induced damage. Mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 61 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…4B). Considering the important role of TGEV-induced apoptosis in host response to TGEV infection (Wang et al 2022), the expression patterns of differentially expressed miRNAs involved in apoptosis were analyzed. Among them, the expression of miR-181 markedly reduced after PCP and TGEV infection, and the result was also confirmed by Real-time PCR ( P < 0.001) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4B). Considering the important role of TGEV-induced apoptosis in host response to TGEV infection (Wang et al 2022), the expression patterns of differentially expressed miRNAs involved in apoptosis were analyzed. Among them, the expression of miR-181 markedly reduced after PCP and TGEV infection, and the result was also confirmed by Real-time PCR ( P < 0.001) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the low efficacy, cytotoxicity, and viral resistance of synthetic antiviral drugs such as Moroxidine, Ribavirin, and Ganciclovir (Märtson et al 2022, Yu et al 2016), natural antiviral drugs are considered easy to accept because of their low toxicity and low price (Ghosh et al 2009). PCP has been proven to have pharmacological effects such as antiviral, antibacterial, anti-inflammatory, and anti-tumor effects (Wang et al 2022). Therefore, we conducted TGEV challenge on weaned piglets and then treated them with PCP.…”
Section: Discusionmentioning
confidence: 99%
“…This complex then binds to anti-oxidant response elements (ARE) located in the promoter region of various cytoprotective genes to promote their transcription and induce the expression of a series of cell protective genes, such as NQO1, HO-1, SOD, CAT, GSH-Px, exerting an anti-oxidative stress role [43]. Previous study had demonstrated that EUG could attenuate transmissible gastroenteritis virus-induced oxidative stress and apoptosis through the ROS-NRF2-ARE signaling pathway [23]. In this study, both in vivo and in vitro data showed that EUG activated NRF2, enhanced its nuclear translocation, and induced the expression of cytoprotective proteins NQO-1 and HO-1.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has demonstrated that EUG could reduce oxidative stress through activating the KEA1-NRF2 signaling pathway to alleviate colitis [22]. Additionally, EUG has been found to attenuate transmissible gastroenteritis virus-induced apoptosis through the ROS-NRF2-ARE signaling pathway [23]. So far, there has been no report to determine whether EUG has a protective effect on damaged pancreatic β cells in T1DM.…”
Section: Introductionmentioning
confidence: 99%
“…Cleaved GSDMD forms membrane pores, leading to cytokine release and pyroptotic cell death. It has been reported that eugenol treatment inhibits apoptosis during TGEV infection . Nonetheless, we are still lacking a complete understanding of the functions of eugenol in TGEV-induced intestinal epithelial cell death, particularly in pyroptosis.…”
Section: Introductionmentioning
confidence: 99%